The Use Of Artificial Intelligence Technology To Improve Students’ Learning Effectiveness in The Digital Era - Muh. Putra Pratama; Muh. Priawibawa Gandatama (Indonesian Journal of Educational Technology, 2026)
This study aims to analyze the utilization of Artificial Intelligence (AI) technology in improving students’ learning effectiveness at SMP Negeri 1 Sanggallangi, North Toraja Regency. AI technology is considered useful in supporting the learning process because it can provide explanations, practice questions, feedback, and access to additional learning resources. This research used a quantitative descriptive approach involving 60 students from Grades VII, VIII, and IX. Data were collected through pre-test and post-test scores, questionnaires, and identification of learning challenges. The results showed that students’ mean score increased from 68.25 in the pre-test to 81.40 in the post-test. Students’ responses toward the use of AI technology were also categorized as high, with an average percentage of 84.0%. These findings indicate that AI technology can improve students’ understanding, motivation, participation, and independent learning. However, several obstacles were found, including limited internet access, limited digital devices, low digital literacy, dependence on AI-generated answers, and limited teacher training. Therefore, AI should be used as a learning support tool under teacher guidance.